The impact of hope on attitudes toward politics among residents of the city of Arequipa - Arias, Walter (2019)
This research analyzes the impact of hope on attitudes toward politics among residents of the city of Arequipa, Peru. The Attitudes Toward Politics Questionnaire and the Herth Hope Index (HHI) were administered to a cluster sample consisting of 875 adults (47,54 % males and 52,46 % females) with an average age of 38 years who lived in eleven districts of the city of Arequipa. Data was processed using a descriptive, comparative and correlational design. The results show that hope and attitudes toward politics differ significantly according to the education level.